(untitled) (Revista Argentina de Cirugía, 2026)
Background: Inguinal hernia repair (IHR) in older adults appears to be associated with a higher rate of complications. As the incidence of complicated hernias, morbidity and mortality are higher in this age group, the management of these patients is still a matter of debate. Objective: The aim of this study was to compare the results of IHR in patients < than 75 years versus those 75 years of age or older. Material and methods: We included a consecutive series of patients undergoing IHR from January 2013 to December 2022, with a minimum follow-up of 6 months. Older adults were defined as patients of 75 years of age or older and the sample was divided into two groups, G1: patients < 75 years of age and G2: patients 75 years of age or older. The demographic and operative variables and the postoperative outcomes were analyzed. Results: A total of 2739 IHR procedures were performed in 2089 patients, 1744 (83.5%) in G1 and 345 (16.5%) patients in G2. Emergency IHR was more common in G2: 9.2% vs. G1: 1.9% (p < 0.001). The overall rate of complications was similar in both groups; however, there were more surgical site events in G2 (G1: 4.9% vs. G2: 8.7%; p = 0.004). The recurrence rate was similar in both groups. Two patients died (0.5%). Both patients were in G2(p = 0.03) and presented strangulated hernias requiring emergency surgery. Conclusions: Emergency surgery is more frequently required in patients ≥ 75 years of age with inguinal hernia.